Modification of Helicobacter pylori outer membrane protein expression during experimental infection of rhesus macaques - Solnick, Jay V. (National Academy of Sciences, 2004)
Clinical isolates of Helicobacter pylori show marked diversity, which may derive from genomic changes that occur during the often lifelong association of the bacterium with its human host. We used the rhesus macaque model, together with DNA microarrays, to examine genomic changes in H. pylori that occur early during experimental infection. Microarray analysis showed that H. pylori recovered from challenged macaques had deleted babA, a member of a large family of paralogous outer membrane proteins (OMPs) that mediates attachment of H. pylori to the Lewis B blood group antigen on gastric epithelium. In some cases the babA gene was replaced by babB, an uncharacterized OMP that is closely related to babA. In other cases the babA gene was present but was not expressed because of alteration in dinucleotide CT repeats in the 5′ coding region. In either case, strains lacking babA did not adhere to Lewis B, which is expressed on macaque gastric epithelium. Absence of babA and duplication of babB was also seen in H. pylori isolates derived from human clinical samples, suggesting that this gene conversion event is not unique to experimentally infected rhesus monkeys. These results demonstrate in real time with a relevant animal model that H. pylori regulates OMP expression in vivo by using both antigenic variation and phase variation. We suggest that changes in babA and babB after experimental infection of macaques represent a dynamic response in the H. pylori outer membrane that facilitates adherence to the gastric epithelium and promotes chronic infection.